Ancora un apporto per la storia della miniatura tolosana del XIV secolo: una nuova attribuzione per le miniature del MS 45 (vol. 1) del Corpus Christi College di Cambridge - Bilotta, María Alessandra (De Medio Aevo, 2022)
The study of the illumination of the MS 45 (vol. 1), preserved in the library of Corpus Christi College in Cambridge, has made it possible to attribute his illustrative apparatus to the hand of the illuminator from Toulouse, active around the middle of the fourteenth century, designated as Master of the Avignon Decretum for having illuminated the ms. 659 of the Municipal Library of Avignon, containing precisely the text of the Decretum Gratiani